Application of Liposome Technology in the Treatment of Leishmaniasis: Past, Present and Future - Amir Mellati; Peyman Asadi; Nahid Soltanloo; Mahdi Fakhar; Seyedeh Hoda Alavizadeh; Javad Akhtari (Journal of Mazandaran University of Medical Sciences, 2023)
Leishmaniasis is one of the most common parasitic diseases in tropical and subtropical regions worldwide and poses a threat to public health. According to the World Health Organization (WHO), the number of leishmaniasis cases worldwide is estimated at 12 million, and the number of people at risk is 350 million. However, leishmaniasis therapies have their limitations, and today nanoparticle delivery systems such as liposomes are used. Liposomes are bilayered structures made of phospholipids and cholesterol, which contain hydrophilic and hydrophobic components in their structure and enable the uptake of hydrophobic, hydrophilic, or amphiphilic compounds. Since the leishmaniasis parasite is predominantly found in macrophages, drug delivery systems improve the therapeutic index of anti-leishmaniasis drugs and reduce the effective dose and toxic off-target effects of non-specific biodistribution. Targeted liposomal drug delivery systems are achieved by utilizing their different structural features such as particle size and surface charge and attaching other ligands to the surface of liposomes for targeted drug delivery. Today, sugar-coated liposomes, cationic liposomes, arsenoliposomes and peptide-targeted liposomes are used to deliver traditional anti-leishmaniasis drugs to Leishmania, and due to the importance of nanoliposomes and their many benefits, research continues in this field.